The place and role of the environment in the foreign policy of the Republic of Serbia - Todić Dragoljub (Međunarodni Problemi, 2013)
The paper points to some methodological and terminological dilemmas in defining the framework of the research as well as the linkage of environmental issues with other relevant issues. Based on the provisions contained in the strategic documents and relevant sources of law there have been analyzed factors that determine the place and the role of the environment in the foreign policy and they are as follows: the state of the environment, the policy objectives of the Republic Serbia (RS) in the environmental field, powers for dealing with environmental issues, powers and way of organizing foreign affairs, perspective of the RS membership in the European Union (EU), global and regional challenges in the environmental field, the place of international co-operation in environmental regulations, membership in international organizations in the environmental field, the status of the RS in international treaties in the environmental field, etc. The second part of the paper emphasizes the possibilities of strengthening the environmental role as a subject of co-operation in achieving certain objectives in the foreign policy of the RS. The author argues the thesis that the place and role of the environment in the foreign policy of the RS are not defined in a clear and precise manner. However, it can be said that the general framework is determined in large part by perspective of the RS membership in the EU and specific regional and global issues in the environmental field. [Projekat Ministarstva nauke Republike Srbije, br. 179029: Srbija u savremenim međunarodnim odnosima: Strateški pravci razvoja i učvršćivanja položaja Srbije u međunarodnim integrativnim procesima - spoljnopolitički, međunarodni ekonomski, pravni i bezbednosni aspekti]